2015
DOI: 10.1371/journal.pone.0141962
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Exposure to Fructose Alters Maternal, Fetal and Neonatal Hepatic Gene Expression and Leads to Sex-Dependent Changes in Lipid Metabolism in Rat Offspring

Abstract: AimFructose consumption is associated with altered hepatic function and metabolic compromise and not surprisingly has become a focus for perinatal studies. We have previously shown that maternal fructose intake results in sex specific changes in fetal, placental and neonatal outcomes. In this follow-up study we investigated effects on maternal, fetal and neonatal hepatic fatty acid metabolism and immune modulation.MethodsPregnant rats were randomised to either control (CON) or high-fructose (FR) diets. Fructos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 84 publications
6
42
0
Order By: Relevance
“…In the present study, HFD induced hepatic de novo lipogenesis through upregulating the expression level of lipid‐regulatory genes, Srebf1 and Ppara , in the HFD1 and HFD2 groups. The present data agree with the results of Clayton et al () who reported that fructose‐fed mother rats at postnatal day 10 demonstrated an increase in PPAR‐α. In contrast, Nagai et al () concluded that fructose or its metabolites downregulate the expression of Ppara in primary cultured hepatocytes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, HFD induced hepatic de novo lipogenesis through upregulating the expression level of lipid‐regulatory genes, Srebf1 and Ppara , in the HFD1 and HFD2 groups. The present data agree with the results of Clayton et al () who reported that fructose‐fed mother rats at postnatal day 10 demonstrated an increase in PPAR‐α. In contrast, Nagai et al () concluded that fructose or its metabolites downregulate the expression of Ppara in primary cultured hepatocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, induction of hepatic triacylglycerol synthesis observed in this study is mediated by SREBP that binds to the sterol regulatory elements of the lipogenic genes activating their transcription (Horton, Goldstein, & Brown, ). The current results are in harmony with those of Nagai et al (); Kanuri, Spruss, Wagnerberger, Bischoff, and Bergheim (); Spruss, Kanuri, Uebel, Bischoff, and Bergheim (); Nomura and Yamanouchi (); and Clayton, Vickers, Bernal, Yap, and Sloboda ().…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in a long-term study [18], we reported that maternal fructose intake produced adverse effects (impaired insulin signal transduction, hyperinsulinemia, and hypoadiponectinemia), which could only have originated during intrauterine development since fructose administration was strictly confined to the pregnancy period. Recently, Clayton et al (2015) have confirmed that early life exposure to fructose alters maternal and perinatal hepatic gene expression [16].…”
Section: Introductionmentioning
confidence: 94%
“…Recently, Clayton et al. (2015) have confirmed that early life exposure to fructose alters maternal and perinatal hepatic gene expression .…”
Section: Introductionmentioning
confidence: 99%
“…; Clayton et al . ), no studies have investigated the impact of sucrose or HFCS‐55 on hepatic fat content or fatty acid composition. This is significant, as the type of fatty acids stored in the liver, as well as the overall fat content, is known to influence hepatic metabolism and the risk of developing diseases including non‐alcoholic fatty liver disease (NAFLD) (Puri et al .…”
Section: Introductionmentioning
confidence: 99%